(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon our Master Muhammad, the Truthful and Trustworthy, and upon his family and companions altogether. O God, we have no knowledge except what You taught us, that You are the All-Knowing, the Wise. Avoid it, and make us among those who listen to what is said and follow the best of it, and admit us with your mercy among your righteous servants, and bring us out from the darkness of ignorance and delusion to the lights of knowledge and knowledge, and from the doubts to the gardens of closeness. And after:Indeed, Allah  sent His Prophet  to clarify and explain their religion to people, and he delivered the clear message and clarified to the nation the truth of its religion, and explained everything to it, and left it on the white argument its night as its day, and in the book of Allah is the guidance and the light. So if some people claim ignorance in some matters, then this is not an excuse